PRESEPSI MASYARAKAT TERHADAP PEMERATAAN PENGGUNAAN APBD DALAM PEMBANGGUNAN PADA DESA WINONG KABUPATEN TULUNGAGUNG - Maulana Ikhrom Ababil; Hwihanus, Hwihanus (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
This research aims to analyze the effectiveness of the allocation and implementation of the Regional Revenue and Expenditure Budget (APBD) in the education, tourism, road repair, etc. sectors in Winong Village, Tulungaggung Regency. Using qualitative research methods with a case study approach, data was collected through in-depth interviews with heads, and community representatives.. The research results show that the APBD allocation for the education sector is still unbalanced, with more focus on developing physical infrastructure rather than improving the quality of human resources. Apart from that, community participation in the APBD preparation process is still low and is only a formality. The factor of delays in budget disbursement is also an obstacle in the implementation of educational programs, which has a negative impact on program effectiveness. The lack of transparency in budget management adds to the challenges in creating good public accountability. This research concludes that improving the quality of APBD management needs to be supported by improvements in determining allocation priorities, increasing public participation, more efficient management of budget disbursement, and higher transparency. Recommendations are given to local governments to pay more attention to balancing budget allocations and involve the community more substantially in the decision-making process.